A practical three‐dimensional plasticity model for cyclic degradation of soil in earthquake loading applications - Qiu, Zhijian; Prabhakaran, Athul; Zhou, Yan‐Guo; Elgamal, Ahmed (Earthquake engineering & structural dynamics, 2023)
A practical yet realistic three‐dimensional (3D) constitutive model is presented for modeling the cyclic degradation behavior of soil. Such response can be attributed to pore pressure build‐up and loss of cementation, among other stiffness and strength degradation mechanisms. Extending an existing multi‐yield surface (MYS) plasticity formulation, the cyclic degradation model (CDM) is developed by incorporating a novel degradation logic in terms of accumulated plastic strain or as prescribed by the user. Thereafter, the CDM is implemented into a computational framework (OpenSees), and Finite Element (FE) calibrations are undertaken to match the available experimental data at the element and system levels. A generally good agreement between the FE simulations and centrifuge test data demonstrates the CDM's capabilities to simulate the seismic response of sloping sites. Using the calibrated model properties, full 3D FE simulations of a large‐scale multi‐span bridge configuration, motivated by details of an actual bridge system in sloping ground, are conducted to highlight the underlying response mechanisms. In addition, computed results including and precluding the effects of cyclic degradation are directly compared and discussed. It is shown that loss of soil strength and stiffness play a noticeable role in the resulting ground and bridge response. Overall, the newly developed constitutive model and findings are of importance for a wide range of soil formations where cyclic degradation occurs under earthquake loading.